Online Contract Worker Recruitment System at PT Prospera Utama Officers - Nuraisyah, Euis Siti; Lisnawati, Dewi; Jasuma, Octavia Noer (Pandawan, 2020)
Human Resources (HR) One of the main keys in the process of finding a professional and qualified workforce. In order to attract attention to applicants, namely information sent through the website so that information can be accessed and choose people who meet job requirements. All companies in any industry can benefit from contingency or maintain professional recruitment or outsourcing processes for recruitment agencies. The employee recruitment system receives importance in the process of inputting and processing, because it makes it easier for the admin to input the ongoing recruitment and selection process. However, the recruitment system is currently related to anything related to data because the paper is scattered. From these considerations, it is necessary to develop the recruitment so that it can be accessed on the system so that it becomes more systematic, organized. In the development of this recruitment system using the method of swot analysis and elicitation. And use one of the PHP programming language, the data base-server uses MySQL. The results achieved from the analysis of the system used by the author is to use UML (Unified Modeling Language). The results of this study are recruitment systems that can be stored more neatly and help the admin when inputting recruitment during the selection process.